South elevation of the Kumbheshwar Mahadev temple - Temples of India Project Team (Jio Institute, 2024)
South Elevation of the Kumbheshwar Mahadev temple. The shikhara above the main shrine has only one tier remnant whereas the shikhara above the mandapa has been replaced by a crude dome. Principal niches of the temple exterior wall house Natesha, Andhakasuravadh, Chamunda. There is a shivlinga in the temple which is under worship.